Microwave assisted extraction of pineapple peel and core / Syazwani Abdul Halim - Abdul Halim, Syazwani (2017)
Ananas Comosus is an important tropical fruit grown extensively and consume by people around the world as dried product, jam, juice, fresh fruit and jelly. However, some part of fruit like peel, core and crown were considered as waste and no value that being disposed to landfill or for composting. The aims of this study are to determine the total phenolic compound in pineapple peel and core and determine the effect of microwave power on extraction process. The peel and core of pineapple were washed in sodium hypochlorite, removed and finely cut and then dried in oven for 50°C. After that, the sample was stored in dark bag. For extraction process, 1.5 g powder was soaked in solvent, adjusted the pH and extracted with different microwave power of 180W, 300W and 450W and lastly cooled, filter, also centrifuged for 15min. The analysis can be carried out next using UVSpectrophotometer and the results obtained were compared with gallic acid standard curve. The microwave power for 180W, 300W and 450W and extraction time 2min and 3min were manipulated. The highest extraction point obtained for peel was 3min at 180W. Meanwhile, the core had the highest extraction of total phenolic compound was 2min at 300W and the optimum condition expressed for all parameter at 300W. From the result obtained, it have demonstrated that phenolic compound is able to extract using the methods of microwave assisted extraction. In the future, to improve the accuracy of the results obtained throughout the experiment, the experiment need to be apply at medium microwave power with shorter extraction time. This can help in reduce the cost and save the energy. Besides that, rather than use ethanol as solvent, the combination of solvent like ethanol-water might be more efficient and recommended to use new extraction techniques other than MAE for natural substance.